Process Capability Analysis Made Simple Through Graphical Approach - Prabhuswamy, M.S.; Nagesh, P. (Kathmandu University Journal of Science, Engineering and Technology, 2007)
The statistical techniques can be used to quantify the variability of the manufacturing process. The process capability analysis helps in quantifying the process variability and assists manufacturing by reducing the variability. Process capability of a manufacturing process can be assessed through the computations of various process capability ratios. Graphical approach can be extended and used to compute capability ratios. A graphical approach of the process capability study is a presentation of process capability parameters in the form of graphs and gives quick information for further computation and analysis. The process capability can be measured and analyzed through the computations of various process capability indices by analytical methods. This involves more computations and time consuming and not user-friendly. The mean and grand mean computations are replaced by median and grand median. Graphical method of computations of median, grand median and average range is developed. Graphical approach can be used for process capability measurement. The graphical approach of process capability study makes it easier to assess the variability of the manufacturing process with less computation and consumes less time and makes user-friendly analysis. The process capability results using median has less affected by extreme values. The median chart indicates on-line variability. If, the control limits are introduced to median chart it performs like average and range chart with fewer computations and consumes less time. This approach helps to worker in the shop floor to assess the process.